Celiac Artery Compression After a Spine Fracture, and Pericardium Rupture After Blunt Trauma: A Case Report from a Single Injury - Joongsuck Kim; Hyun Min Cho; Sung Hwan Kim; Seong Hoon Jung; Jeong Eun Sohn; Kwangmin Lee (Journal of Trauma and Injury)
Celiac artery compression is a rare condition in which the celiac artery is compressed by the median arcuate ligament. Case reports of compression after trauma are hard to find. Blunt traumatic pericardium rupture is also a rare condition. We report a single patient who experienced both rare conditions from a single blunt injury. An 18-year-old woman was brought to the trauma center after a fatal motorcycle accident, in which she was a passenger. The driver was found dead. Her vital signs were stable, but she complained of mild abdominal pain, chest wall pain, and severe back pain. There were no definite neurologic deficits. Her initial computed tomography (CT) scan revealed multiple rib fractures, moderate lung contusions with hemothorax, moderate liver injury, and severe lumbar spine fracture and dislocation. She was brought to the angiography room to check for active bleeding in the liver, which was not apparent. However, the guide wire was not able to pass through the celiac trunk. A review of the initial CT revealed kinking of the celiac trunk, which was assumed to be due to altered anatomy of the median arcuate ligament caused by spine fractures. Immediate fixation of the vertebrae was performed. During recovery, her hemothorax remained loculated. Suspecting empyema, thoracotomy was performed at 3 weeks after admission, revealing organized hematoma without pus formation, as well as rupture of the pericardium, which was immediately sutured, and decortication was carried out. Five weeks after admission, she had recovered without complications and was discharged home.